A REVIEW TO THE GENESIS, EVOLUTION AND CLASSIFICATION OF THE SOILS FORMED ON LIMESTONES AND DOLOMITES IN THE REPUBLIC OF MACEDONIA - Tatjana Mitkova*, Mile Markoski (CONTRIBUTIONS, Section of Natural, Mathematical and Biotechnical Sciences, MASA, Vol. 40, No. 1, pp. 63–72 (2019, 2019)
The soils formed on limestones and dolomites in different locations in the Republic of Macedonia have been ex amined. These soils differ in their genesis, evolution and properties from soils formed on other substrates and have a number of specificities, whereby all their properties largely depend on the parent material. They occupy much of the soil cover of the Republic of Macedonia. The field examinations were carried out according to the generally accepted method in our country [1, 2]. Most of them are under high mountainous pastures, some plots are under meadows and fields. They have great importance for the faster development of some industries in the country, forestry, tourism, as well as the agricultural development in the hilly and mountainous underdeveloped areas in our country.
Keywords: soils formed on limestones and dolomites; genesis; evolution; classification